Viewing Advertising through the Lens of Faith: Finding God in Images of Mammon - Kelso, Tony (Implicit religion, 2006)
Various scholars have noted connections between traditional Protestantism and advertising in the United States. Not only did the two institutions inform one another as modern advertising emerged and matured, but, arguably, the two systems also exhibit parallel rhetorical formats and functions today. In this qualitative study, it is suggested that a shift in emphasis, from advertising's relationship to explicit religion to its interaction with implicit religiosity, could provide fresh insights. This framework was explored through focus group interviews, participant journal entries, and one-on-one, in-depth interviews with Protestants from three mainline congregations. The findings show that some of the participants can, on occasion, touch the spiritual realm through transactions with advertising. Indeed, it is contended that, although they belong to formal religious organizations, these respondents can also engage in practices associated with implicit religion. At the same time, the interviewees also indicated they have little awareness of how advertising perpetuates the economic status quo. Displaying hegemony at work, they are seemingly able to pursue both explicit and implicit religious experiences and support their market-driven culture without bearing significant cognitive dissonance. The paper makes the case that advertising can sometimes function as a vehicle for helping to reconcile this apparent conflict.